2022
DOI: 10.1017/s0022215122001621
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transoral approach to the parapharyngeal space: technical nuances and preliminary results

Abstract: Objective Surgical management is the mainstay of treatment for tumours in the parapharyngeal space. This study aimed to evaluate the indications, limits and technical nuances of the endoscopic transoral approach. Method Thirteen patients with parapharyngeal space tumours that were treated between May 2017 and November 2020 were included in this retrospective study. Results All patients underwent surgery for complete oncological resection except one patient who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Studies have shown that acupuncture at the Lianquan (RN 23) can improve the myoelectricity of the muscles of the hyoid bone and promote elevation of the throat. 16 Since the distribution of the muscles of the pharynx is deep and their internal structure is complex, 15 there are few acupuncture protocols that can fit the corresponding posterior suspension of the hyolaryngeal complex. In “Tongguan Liqiao” acupuncture method, deep needling at the Yifeng (SJ 17) and Wangu (GB 12) can reach the area of the pharyngeal muscles.…”
Section: Aligning With the Anatomy Of Swallowing Function And Deep Ne...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that acupuncture at the Lianquan (RN 23) can improve the myoelectricity of the muscles of the hyoid bone and promote elevation of the throat. 16 Since the distribution of the muscles of the pharynx is deep and their internal structure is complex, 15 there are few acupuncture protocols that can fit the corresponding posterior suspension of the hyolaryngeal complex. In “Tongguan Liqiao” acupuncture method, deep needling at the Yifeng (SJ 17) and Wangu (GB 12) can reach the area of the pharyngeal muscles.…”
Section: Aligning With the Anatomy Of Swallowing Function And Deep Ne...mentioning
confidence: 99%
“…At the same time, deep needling of Yifeng (SJ 17), Wangu (GB 12), and Fengchi (GB 20) toward the laryngeal prominence can reach the gap between the anterior and posterior stylohyoid, 11 22 23 which is also the area where cranial nerves IX–XII for cranial nerve penetration and neck branches. 15 The cranial nerves IX–XII is directly related to functions such as elevation of the throat and airway cough reflex during swallowing, 12 24 and stimulating this area through needling can effectively promote the recovery of swallowing function by providing surrounding nerve stimulation.…”
Section: Aligning With the Anatomy Of Swallowing Function And Deep Ne...mentioning
confidence: 99%